2015
DOI: 10.1097/rhu.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia and Obesity

Abstract: Compared with normal-weight patients, obese FM patients are more disabled, report more medical comorbidities, exercise less, have a higher incidence of abuse, report increased depressive symptoms, and take more medications for FM. Bivariate analysis showed association of increasing BMI with the Health Assessment Questionnaire Disability Index (not FM impact questionnaire) and depression. We confirm that the prevalence of overweight and obesity is high in FM and believe that physicians treating FM should be awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 52 publications
4
31
3
Order By: Relevance
“…Additionally, after adjustment for age and education, no significant positive correlation was found between BMI and TPC in their study. In agreement with the finding by Yunus, Arslan & Aldag (2002) , Gota, Kaouk & Wilke (2015) reported no difference in pain scores among normal weight, overweight and obese FMS patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, after adjustment for age and education, no significant positive correlation was found between BMI and TPC in their study. In agreement with the finding by Yunus, Arslan & Aldag (2002) , Gota, Kaouk & Wilke (2015) reported no difference in pain scores among normal weight, overweight and obese FMS patients.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Senna et al (2012) evaluated weight reduction in obese patients with FMS and reported that patients with weight-loss had better depression scores. On the contrary, Gota, Kaouk & Wilke (2015) , Yunus, Arslan & Aldag (2002) and Okifuji et al (2010) did not find any association between BMI and depression and anxiety.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This phenomenon may be ascribed to a higher prevalence of lifetime stress and sleep disorders in individuals with a higher socioeconomic status. [ 46 ] Because sedentary occupation leads to metabolic syndrome and diabetes, either of which can also result in physiological pain, depression, and suicide, [ 47 , 48 ] introducing health behaviors to reducing sedentary behavior was suggested as an effective intervention [ 49 ] to manage and cope with stress. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Demographic and social characteristics associated with the presence of FM are female, divorced, low income, and no high school diploma. Psychological factors associated with this syndrome include: somatization disorder, anxiety, and personal or family history of depression (Gota, Kaouk, & Wilke, 2015). In Taiwan, the prevalence of FM was 6.7 % and 9.8 % based on the population of one small town in the middle of Taiwan which was higher than nearby countries such as Korea (1.7%-2.3%) and Japan (0.51-2.04%) (Chen, Guo, You, Liaw, & Kuo, 2008;Kim, Kim, & Kim, 2012;Nakamura et al, 2014;Toda, 2007).…”
Section: Introductionmentioning
confidence: 99%